Design, Construction and Performance Evaluation of a Manual Cum Motorized Orange Juice Extracting Machine - Istifanus, A. B.; Bulus, K.; Adimbo, M. A.; Ardo, H. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
A manual cum motorized operated juice extractor was designed and fabricated using locally sourced materials. Polytetrafluoroethylene (PTFE) a synthetic fluoro polymer was used in the construction of the screw shaft and stainless steel for the extraction chamber. Rotational motion needed by the screw shaft to compress and transport the fruits was supplied both manually cum motorized to the machine through a handle and electric motor device of 10w because this has capacity to handle the performance operation. The screw shaft crushes, squeeze and facilitate the movement of residues to the waste outlet while the juice passes through the screen to the juice collector. Tests were carried out to investigate the performance of the machine on the basis of juice yield, extraction efficiency and extraction loss. The fruits were washed and weights (1kg, 1.5kg and 2kg respectively) of fruit slice (8 and 16 slices) were then processed using the extractor to extract the Juice. The juice yield, extraction loss and extraction efficiency were determined by standard Formula and methods. Maximum juice yield of 64.6 % extraction efficiency of 68.2 % and Corresponding extraction loss of 7.05 % were obtained from the 16 slice lengths orange fruits were used for the test. The juice produced from the extractor was of good quality which further proves the effectiveness of the extractor. The manual fruit juice extractor is cheap(N48770), durable and cost of operation is low while motorized juice extractor is faster in terms of operation or extraction efficiency and extraction loss, and also it could be used by an average Nigerian household and small-scale farmers.